ANALYSIS OF INFORMED CONSENT AS THE LEGAL PROTECTION OF PHYSICIAN RELATIONSHIPS AND PATIENTS IN MALPRACTICE CASES: (Case Study of Supreme Court Decision Number 21/Pdt.G/2018/PN Mnk) - Irwan Lazuardi; Siti Marwiyah (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
The implementation of medical behavior involves two parties, namely doctors or other health workers as executors of medical behavior and patients as recipients of medical behavior bound in Informed Consent. However, the occurrence of malpractice cases causes the role of Informed Consent to be doubted both from the patient and doctor's side because the validity of Informed Consent becomes biased if there is no legal basis and knowledge of the agreement. The research aims to analyze the role of Informed Consent as legal protection for the relationship between doctors and patients in cases of malpractice and to analyze the legal remedies given to doctors and patients in malpractice cases in Supreme Court Decision Number 21/Pdt.G/2018/PN Mnk. This type of research is normative research using a statutory-based approach. The process of collecting data through a literature study with an analysis of legal materials through a qualitative descriptive analysis. The results of the study prove that the role of informed consent as legal protection is not entirely a determinant of a case being declared as malpractice. From the decision Number 21/Pdt.G/2018/PN Mnk it was concluded that the existence of Informed Consent could not be used as legal protection because the doctor was proven to have made a mistake in setting the drug dosage. Related to the legal protection given to patients who are victims of malpractice is the Health Law no. 23 of 1992 which gives everyone the right to ask for compensation for mistakes and negligence committed by health workers.